Facial skin pigmentation is not related to stratum corneum cohesion, basal transepidermal water loss, barrier integrity and barrier repair. (21st January 2015) - Voegeli, R.; Rawlings, A. V.; Summers, B.
Synopsis Objective Hypotheses have been developed for the evolutionary selection of skin pigmentation one of which relates to improved skin barrier function. The aim of this study was to compare facial skin condition on photoexposed (cheek) and photoprotected (post‐auricular) sites of naturally pigmented subjects of different ethnicities (Fitzpatrick skin phototypes II/III and V/VI) and Albino African subjects to understand better the relationship between facial stratum corneum (SC) barrier function, skin surface pH and skin pigmentation. Methods Expert grading of skin conditions, capacitance, skin surface pH and skin barrier function measurements were performed. For the latter, transepidermal water loss (TEWL) measurements before (basal TEWL), after 3, 6 and 9 consecutive tape strippings (SC integrity) and 3.5 and 24 h post tape stripping (barrier recovery) were taken. Amounts of SC protein removed during stripping were estimated using infrared densitometry (SC cohesion). Results Firstly, correlation analysis of the biometric data of the Black African and Caucasian subjects showed there to be no relationship between skin surface pH and ITA° values nor pH and ITA° with basal TEWL. Neither skin surface pH nor ITA° correlated with SC integrity and barrier recovery measurements, but skin surface pH correlated with SC cohesion. ITA° values were correlated with skin hydration. Secondly, on comparing the three ethnic groups, severe skin photodamage was observed in the Albino African subjects and their SC was thicker. Whereas their basal TEWL was elevated, superior values for SC integrity and barrier recovery were measured. No differences in basal TEWL, SC integrity and barrier recovery were found between the other two subject groups. Equally, SC cohesion and skin surface pH values were similar among the three groups. Conclusion There was no relationship between ITA° values and basal TEWL, SC integrity, SC cohesion and barrier recovery, but ITA° was correlated with skin hydration. Skin surface pH, irrespective of ITA° values, correlated with SC cohesion, indicating a greater intracorneal cohesion at lower pH values. Thus, pigmentation has no effect on SC barrier properties but was related to skin hydration. On comparing the three ethnic groups, Albino African SC was found to be superior to the Caucasian and Black African subjects in terms of SC integrity and barrier recovery but not basal TEWL. The Albino African subjects also have a thicker SC which contributes to their better SC integrity. No differences in skin barrier functionality or skin surface pH were observed for the other two groups. Skin hydration was, however, greatest in the Black African subjects. Our data support the evolutionary hypothesis that pigmentation protects the skin from UV irradiation and thereby the skin barrier but not the skin pigmentation‐/pH‐driven adaptive skin barrier hypothesis.